The benefits and limitations of using ultrasonography to supplement anatomical understanding. Issue 3 (26th October 2012) - Sweetman, Greg M.; Crawford, Gail; Hird, Kathryn; Fear, Mark W.
Abstract Anatomical understanding is critical to medical education. With reduced teaching time and limited cadaver availability, it is important to investigate how best to utilize in vivo imaging to supplement anatomical understanding and better prepare medical graduates for the proliferation of point‐of‐care imaging in the future. To investigate whether using short sessions of in vivo imaging using ultrasonography could benefit students' anatomical knowledge and clinical application, we conducted a 2‐hour session on abdominal anatomy using ultrasonography in small groups of five to six students, for both first‐ and second‐year student cohorts. Individual feedback was collected to assess student perceptions. To measure retention and understanding, a short examination containing ultrasound images and questions and performance of a clinical skill (gastrointestinal' tract examination) were assessed. Ultrasonography sessions were highly valued by the students, with 90% of the students reporting their understanding was improved, and over 70% reporting increased confidence in their anatomical knowledge. However, the assessments showed no appreciable impact on skills or understanding related to abdominal anatomy and examination. We conclude that the risk associated with limited exposure increasing confidence without increasing skills remains real and that in vivo imaging is not effective when used as a short adjunct teaching tool. The widespread use of ultrasonography means finding the best way to incorporate ultrasound into medical education remains important. To this end, we are currently implementing an extended program including echocardiography and multiple anatomical sessions that will determine if frequency and repetition of use can positively impact on student performance and understanding. Anat Sci Educ. © 2013 American Association of Anatomists.